Alumni Revival Issue 2: August 2023 - Morshidi, Nur Anisya; Syed Akil, Sharifah Nur Amirah; Guyang, Martina Emelda; Umbat, Anjeli; Jack, Suriani (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Alumni Revival means the process of reconnecting with and engaging former students or graduates of an educational institution, such as a university or college, who have lost touch with the school or their fellow alumni, is referred to as alumni revival. It include attempts to rekindle alumni connections, devotion, and commitment, eventually establishing a stronger alumni community. Alumni revival projects seek to reintegrate alumni into the institution's activities by providing chances for them to reconnect, network, and contribute to the growth and development of their alma mater. This might involve organising alumni-specific events, reunions, and networking opportunities, as well as employing communication techniques to keep alumni informed about the institution's accomplishments, initiatives, and current developments. Fostering a sense of pride and loyalty among alumni also entails emphasising their successes, recognising their efforts, and exhibiting the success stories of other graduates. By revitalising the alumni community, universities may draw into their alumni network's aggregate expertise, resources, and support, benefiting both the institution and its graduates. Overall, alumni revival is about rekindling the relationship between an educational institution and its former students, reigniting their passion and involvement, and establishing a strong and engaged alumni community that can contribute to the institution's success while also providing opportunities for personal and professional growth for its graduates.